Learning to dialogue in the preschool classroom: a theoretical and pedagogical proposal - Jaimes de Casadiego, Gladys (Rastros Rostros, 2024)
The recognition of the importance of dialogue in the development of the child's potential raises the need to deepen the understanding of this strategy of discursive activity in order to support proposals for the transformation of pedagogical practices related to the mother tongue at the beginning of schooling.